Analysis of Population Genetic Diversity and Genetic Structure of Schizothorax biddulphi Based on 20 Newly Developed SSR Markers - Nie, Zhulan; Ren, Yongli; Zhang, Lirong; Ge, Rui; Wei, Jie (Frontiers in Genetics, 2022)
To protect the germplasm resources of Schizothorax biddulphi, we developed and used the 20 pairs of polymorphic microsatellite primers to analyze the genetic diversity and structure of populations. A total of 126 samples were collected from the Qarqan River (CEC), Kizil River (KZL), and Aksu River (AKS) in Xinjiang, China. The results showed that 380 alleles were detected in 20 pairs of primers and the average number of alleles was 19.0. The effective allele numbers and Nei's gene diversity ranged from 1.1499-1.1630 and 0.0962-0.1136, respectively. The Shannon index ranged suggesting low levels of genetic diversity in all populations. The genetic distance between the CEC and AKS populations was the largest and the genetic similarity was the smallest. There was a significant genetic differentiation between CEC and the other two populations. The UPGMA clustering tree constructed based on population genetic distance, and the clustering tree constructed by individuals showed that the AKS population and KZL population were clustered together and the CEC population was clustered separately. Also, the group structure analysis also got the same result. It can be seen that although the three populations of S. biddulphi do not have high genetic diversity, the differentiation between the populations was high and the gene flow was limited, especially the differentiation between the CEC population and the other two populations. This study not only provided genetic markers for the researches of S. biddulphi, but the results of this study also suggested the need for enhanced management of S. biddulphi populations.